Understanding the Cross of Emperor Constantine (2020)
Ancient and modern authors such as Eusebius of Caeserea, Flavius Josephus, Lanctatius, Cutaru, Nicholson, Torres and several others have variously discussed Emperor Constantine's conversion to the Christian religion. While some have argued about the sincerity of his conversion consequent on his tolerance and participation in some non-Christian rites, others contend that his conversion to the Christian faith was not in doubt. This paper intends to examine Emperor Constantine and his cross, with a view to interrogating his strategy of adopting the cross as a means to achieve victory. The study argued that Constantine's desire to defeat Maxentius, motivated him to accept and adopl a strategy, albeit unpopular, in order to deal a decisive blow on the enemy. This study further argued that the cross of Emperor Constantine consequently had a great impact on the Roman political, cultural and religious spaces. The study adopts a historical methodology as it considered this question of the cross in antiquity. Further studies may critically examine the roles of succeeding emperors to the fate of Christianity in the Roman Empire.